Negotiating Models of The Identity of Minorities Religious Follower in The South Padang District of Padang City - Sefriyono, Sefriyono (IAIN Ponorogo, 2018)
Abstract: The presence of numerous religions in the midst requires negotiation. Negotiation is the way an individual or groups get the recognition from others. In negotiations, each group tries to reduce their bargaining position for an agreement in order to get the benefits for both parties. Negotiation models employed by the follower of religious minorities like Christian, Catholic, and Buddha in the mid of Muslim majority in South Padang District are: first, Church without the symbol of cross–Catholic do not mind to take off their cross symbol in their church so that the church looks like a regular building. This action is done by Catholic to honor the Minangkabau sensitivity on the establishment of church; second, using hijab for non-Muslim students–wearing â€œhijabâ€ to minimize their differences with the Muslim Students, especially in public school; third, the housing ritual for Christian. Its can be done by the obeying of them to the local regulations and negotiation with local leader; fourth, Buddhist was not stunted become the chief committee of the establishing of mosque; fifth, the sacrificial meat not only enjoyed by Muslim but also non-Muslim. Although, the negotiation on the establishing the new church difficult to be realized, but on the others field like political, education, economic, the negotiation were implemented well.Ø§Ù„Ù…Ù„Ø®Øµ: ÙŠØØªØ§Ø¬ ÙˆØ¬ÙˆØ¯ Ø§Ù„Ø¹Ø¯ÙŠØ¯ Ù…Ù† Ø§Ù„Ø¯ÙŠØ§Ù†Ø§Øª ØÙˆÙ„ Ø§Ù„Ù…Ø¬ØªÙ…Ø¹ Ø¥Ù„Ù‰ Ø§Ù„ØªÙØ§ÙˆØ¶. Ø§Ù„ØªÙØ§ÙˆØ¶ Ù‡Ùˆ Ø§Ù„Ø·Ø±ÙŠÙ‚Ø© Ø§Ù„ØªÙŠ ÙŠØØµÙ„ Ø¨Ù‡Ø§ Ø§Ù„ÙØ±Ø¯ Ø£Ùˆ Ø§Ù„Ù…Ø¬Ù…ÙˆØ¹Ø§Øª Ø¹Ù„Ù‰ Ø§Ù„Ø§Ø¹ØªØ±Ø§Ù Ù…Ù† Ø§Ù„Ø¢Ø®Ø±ÙŠÙ†. ÙÙŠ Ø§Ù„ØªÙØ§ÙˆØ¶ ØªØØ§ÙˆÙ„ ÙƒÙ„ Ù…Ø¬Ù…ÙˆØ¹Ø§Øª Ø£Ù† ØªØ®Ø¶Ø¹ Ù…ÙˆÙ‚ÙÙ‡Ø§ Ù…Ù† Ø£Ø¬Ù„ Ø§Ù„ÙˆØµÙˆÙ„ Ø¥Ù„Ù‰ Ø§ØªÙØ§Ù‚ Ù„Ù„ØØµÙˆÙ„ Ø¹Ù„Ù‰ Ø§Ù„ÙÙˆØ§Ø¦Ø¯ Ù„ÙƒÙ„Ø§ Ø§Ù„Ø·Ø±ÙÙŠÙ†. ÙˆÙ†Ù…Ø§Ø°Ø¬ Ø§Ù„ØªÙØ§ÙˆØ¶ Ø§Ù„Ù…Ø³ØªØ®Ø¯Ù…Ø© Ù…Ù† Ù‚Ø¨Ù„ Ø£ØªØ¨Ø§Ø¹ Ø§Ù„Ø£Ù‚Ù„ÙŠØ§Øª Ø§Ù„Ø¯ÙŠÙ†ÙŠØ© Ù…Ø«Ù„ Ø§Ù„Ù…Ø³ÙŠØÙŠÙŠÙ† ÙˆØ§Ù„ÙƒØ§Ø«ÙˆÙ„ÙŠÙƒÙŠÙ† ÙˆØ¨ÙˆØ°ÙŠÙŠÙ† Ø£Ø«Ù†Ø§Ø¡ Ø£ØºÙ„Ø¨ÙŠØ© Ø§Ù„Ù…Ø³Ù„Ù…ÙŠÙ† ÙÙŠ Ø¬Ù†ÙˆØ¨ Ø¨Ø§Ø¯Ø§Ù†Ø¬ ÙƒÙ…Ø§ ÙŠÙ„ÙŠ: Ø£ÙˆÙ„Ø§Ù‹ØŒ Ù„Ø§ ØªÙƒÙˆÙ† ÙÙ‰ Ø§Ù„ÙƒÙ†ÙŠØ³Ø© Ø±Ù…Ø² Ø§Ù„ØµÙ„ÙŠØ¨- Ø®Ù„Ø¹ Ø§Ù„ÙƒØ§Ø«ÙˆÙ„ÙŠÙƒÙŠÙˆÙ† Ø±Ù…Ø² Ø§Ù„ØµÙ„ÙŠØ¨ ÙÙŠ ÙƒÙ†ÙŠØ³ØªÙ‡Ù… ØØªÙ‰ ØªØ¨Ø¯Ùˆ Ø§Ù„ÙƒÙ†ÙŠØ³Ø© ÙƒØ£Ù†Ù‡Ø§ Ù…Ø¨Ù†Ù‰ Ø¹Ø§Ø¯ÙŠ.Â ØªÙ…Ù‘ Ù‡Ø°Ø§ Ø§Ù„Ø¥Ø¬Ø±Ø§Ø¡ Ù…Ù† Ù‚Ø¨Ù„ Ø§Ù„ÙƒØ§Ø«ÙˆÙ„ÙŠÙƒÙŠÙŠÙŠÙ† Ù„ØªØØ±ÙŠÙ… ØØ³Ø§Ø³ÙŠØ© Ø´Ø¹Ø¨Ø© Ù…ÙŠÙ†Ø§Ø¬ ÙƒØ§Ø¨Ùˆ Ø¹Ù„Ù‰ Ø¨Ù†Ø§Ø¡ Ø§Ù„ÙƒÙ†ÙŠØ³Ø© Ù‡Ù†Ø§Ùƒ. Ø«Ø§Ù†ÙŠØ§ØŒ Ø§Ø±ØªØ¯Ø§Ø¡ Ø§Ù„ØØ¬Ø§Ø¨ Ù„Ù„Ø·Ø§Ù„Ø¨Ø§Øª ØºÙŠØ± Ø§Ù„Ù…Ø³Ù„Ù…ÙŠÙ†- Ø§Ø±ØªØ¯Ø§Ø¡ Ø§Ù„ØØ¬Ø§Ø¨ Ù„ØªÙ‚Ù„ÙŠÙ„ Ø§Ø®ØªÙ„Ø§ÙØ§ØªÙ‡Ù… Ù…Ø¹ Ø§Ù„Ø·Ø§Ù„Ø¨Ø§Øª Ø§Ù„Ù…Ø³Ù„Ù…Ø§Øª ÙˆØ®Ø§ØµØ© ÙÙŠ Ø§Ù„Ù…Ø¯Ø§Ø±Ø³ Ø§Ù„Ø¹Ø§Ù…Ø©. Ø«Ø§Ù„Ø«Ø§ØŒ Ø§Ù„Ø¹Ø¨Ø§Ø¯Ø© Ø§Ù„Ø³ÙƒÙ†ÙŠØ© Ù„Ù„Ù…Ø³ÙŠØÙŠØ© ÙŠÙ…ÙƒÙ† Ø£Ù† ÙŠØªÙ… Ø°Ù„Ùƒ Ø¹Ù† Ø·Ø±ÙŠÙ‚ Ø¥Ø·Ø§Ø¹ØªÙ‡Ø§ Ø¥Ù„Ù‰ Ø§Ù„Ù†Ø¸Ø§Ù… Ø§Ù„Ù…ØÙ„ÙŠ ÙˆØ§Ù„ØªÙØ§ÙˆØ¶ Ù…Ø¹ Ø§Ù„Ø²Ø¹ÙŠÙ… Ø§Ù„Ù…ØÙ„ÙŠ. Ø±Ø§Ø¨Ø¹Ø§ØŒ Ù„Ø§ ÙŠØªÙˆÙ‚Ù Ø£Ù† ÙŠØµØ¨Ø Ø§Ù„Ø¨ÙˆØ°ÙŠØ© Ø±Ø¦ÙŠØ³ÙŠØ© Ø§Ù„Ù„Ø¬Ù†Ø© Ù„ØªØ£Ø³ÙŠØ³ Ø¨Ù†Ø§Ø¡ Ø§Ù„Ù…Ø³Ø¬Ø¯. Ø®Ø§Ù…Ø³Ù‹Ø§ØŒ Ù„ØÙ… Ø§Ù„Ø£Ø¶ØÙŠØ© Ù„Ø§ ÙŠØªÙ…ØªØ¹Ù‡ Ø§Ù„Ù…Ø³Ù„Ù…ÙˆÙ† ÙØØ³Ø¨ Ø¨Ù„ ØºÙŠØ± Ø§Ù„Ù…Ø³Ù„Ù…ÙŠÙ† Ø£ÙŠØ¶Ø§. Ø¹Ù„Ù‰ Ø§Ù„Ø±ØºÙ… Ù…Ù† Ø£Ù† Ø§Ù„ØªÙØ§ÙˆØ¶ Ø¹Ù„Ù‰ Ø¨Ù†Ø§Ø¡ ÙƒÙ†ÙŠØ³Ø© Ø¬Ø¯ÙŠØ¯Ø© ØµØ¹Ø¨ Ù„Ø£Ù† ÙŠØªØÙ‚Ù‚ ÙˆÙ„ÙƒÙ† ÙÙŠ Ù…Ø¬Ø§Ù„Ø§Øª Ø£Ø®Ø±Ù‰ Ù…Ø«Ù„ Ø§Ù„Ø³ÙŠØ§Ø³Ø© ÙˆØ§Ù„ØªØ¹Ù„ÙŠÙ… ÙˆØ§Ù„Ø§Ù‚ØªØµØ§Ø¯ ØªÙ… ØªÙ†ÙÙŠØ° Ø§Ù„ØªÙØ§ÙˆØ¶ Ø¨Ø´ÙƒÙ„ Ø¬ÙŠØ¯.Â Abstrak: Kehadiran banyak agama di tengah-tengah masyarakat membutuhkan negosiasi. Negosiasi adalah cara individu atau kelompok mendapatkan pengakuan dari orang lain. Dalam negosiasi, masing-masing kelompok berusaha mengurangi posisi tawar mereka untuk sebuah perjanjian agar mendapat manfaat bagi kedua belah pihak. Model negosiasi yang digunakan oleh pengikut agama minoritas seperti Kristen, Katolik, dan Buddha di tengah-tengah mayoritas Muslim di Kabupaten Padang Selatan adalah: pertama, gereja tanpa simbol salib - Katolik tidak keberatan melepas simbol salib mereka di gereja sehingga gereja terlihat seperti bangunan biasa. Tindakan ini dilakukan oleh Katolik untuk menghormati kepekaan Minangkabau pada pendirian gereja; kedua, menggunakan jilbab untuk siswa non-Muslim -mengenakan